Tanaman Ramah Lingkungan Selei Kolang Kaling dan Strowberi Mengurangi Konstipasi Pada Ibu Hamil Trimester III - Maryanti, Endang; Butar-Butar, Maria Haryanti; Mariana, Mariana; Aisyah, Putri (Journal of Telenursing (JOTING), 2023)
This research aims to modify canned kolang ingredients into an innovative product that is mixed with strawberries and made into jam which is useful for reducing constipation for pregnant women in the third trimester in the PB Selayang II Health Center Work Area, Medan in 2023. The method used is quantitative research using quasi-experimental methods. design with one group pretest-posttest design. The research has gone through the USU Faculty of Nursing Health Research Ethics approval process with number 2847/VII/SP/2023. The instrument uses a questionnaire containing respondent data/identity and research observation sheets. The research results showed that the results of the paired t test were obtained with a mean result of 19.34 with a t value of 561,000 and a p value of 0.000 in the group of mothers before eating kolang kaling jam and strawberries and then mothers after eating kolang kaling jam and strawberries. In conclusion, kolang kaling and strawberry jam have benefits and functions that can help prevent constipation from pregnant women. Keywords: Pregnant Women, Constipation, Jam